Metastatic Lobular Carcinoma of the Breast Masquerading as Gallstone Disease – A Case Report - Basim Ali; Mehdia Nadeem Rajab Ali; Narmeen Asif; Abdul Ahad Sohail; Sana Zeeshan (Annals of Internal Medicine: Clinical Cases)
The gallbladder is a rare site of breast cancer metastasis. We report the patient case of a 60-year-old woman with isolated metastasis to the gallbladder, which was surgically removed for symptomatic cholelithiasis, with a subsequent new diagnosis of infiltrating lobular carcinoma (ILC) of the breast. ILC tends to metastasize to unusual sites such as the gastrointestinal and genitourinary tracts, but these usually occur concurrently with other more common sites of distant metastasis such as the bone, lungs, and liver. Our case underscores the need for routine histologic examination of gallbladder after cholecystectomy.